Tussen twee stoelen, tussen twee vuren Nederlandse literatuur op weg naar de buitenlandse lezer - Missinne , Lut (Lage Landen Studies, 2018)
The tenth volume of the Lage Landen Studies explores the road of an original Dutch-language book from its original version to the translation that arrives into the hands of a non-native reader. This collection of research articles features literary translations with Dutch as source language. The authors pay special attention to production-specific aspects of the literary transfer process: What are the conditions to make a translation? Who is involved in the process? What part do translators and institutions play? Which norms determine the production and distribution of translated texts? In their contributions on transfer to the German, English, French, Indonesian, Russian and Czech language, the authors mention different aspects that are mainly new to the cultural transfer of Dutch-language literature abroad and/or give new impulses to its research.